The development of the quality management system in terms of knowledge management / Kokybės vadybos sistemų tobulinimas žinių vadybos aspektu - Romualdas Vitkauskas (Mokslas: Lietuvos Ateitis, 2011)
The interaction of quality management and knowledge management are analyzed quite widely in scientific literature and discussed with reference to various models integrating these two management theories. However, there are not enough precise tools that could provide a possibility of improving the quality of products and services through knowledge management. To this end, the article examines the already existing models for the interaction between quality management and knowledge management. The results of a survey on Lithuanian industry show what organizational knowledge is the most important while implementing quality management principles aimed at improving quality. The correlation analysis method showed the relationship between quality management principles (process approach, continual improvement, management, facts) and the factors defining the product and process quality (the extent of determining process execution time, process resources, costs of process stages, indicators for products and/or services, the duration of the process, the extent of measuring indicators, the extent of collecting information on indicators, the extent of collecting information about the costs of the process).